2002
DOI: 10.1016/s1388-9842(02)00090-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and muscle strength training and their effect on quality of life in patients with chronic heart failure

Abstract: Background: There is now evidence that moderate training plays an important role in the treatment of chronic heart failure. No clear instructions exist to date as to how such training programs should be carried out. Aim: to assess the efficiency of a training program including bicycle ergometer training, moderate muscle strength training and the 6-min walk test and their influence on quality of life, anxiety and depression. Methods and results: Patients (67 male, 21 female) underwent a standardized 4-week trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…25 The maximum workload of ergometer training was defined to correspond to the heart rate measured at 60% to 80% of peak oxygen uptake. An initial warmup of 5 minutes at 15 W was followed by training units of 15 to 20 minutes.…”
Section: Humans and Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The maximum workload of ergometer training was defined to correspond to the heart rate measured at 60% to 80% of peak oxygen uptake. An initial warmup of 5 minutes at 15 W was followed by training units of 15 to 20 minutes.…”
Section: Humans and Trainingmentioning
confidence: 99%
“…Exercise capacity before and after the training program was assessed by peak oxygen uptake with a ramp protocol (initial level 25 W, 10-W increase every 10 minutes; Ergoline 900, Marquette/Hellige; Ergoscope, Ganshorn) and by a standardized 6-minute walking test. 25,26 …”
Section: Humans and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…96 The effects of an exercise program on depression in patients with heart failure were examined in 7 studies. [101][102][103][104][105][106][107] The exercise programs varied by type, intensity, frequency, duration, and patients' adherence. Despite the differences, the strength of the evidence was moderate that exercise is effective at decreasing depressive symptoms in patients with heart failure.…”
Section: Effects Of Selective Serotonin Reuptake Inhibitors and Exercisementioning
confidence: 99%
“…25,[33][34][35][36][37][38] No serious adverse events because of exercise were reported across all studies. Large heterogeneity in exercise prescriptions and participants' adherence may explain why some studies showed improvement, whereas others failed to show much effect (d range, .1 to .7).…”
Section: Exercisementioning
confidence: 99%